Electric and mechanical properties of Pb(Fe_0.5Nb_0.5)O_3 ferroelectric ceramics - Zachariasz, Radosław; Ilczuk, Jan (Archives of Acoustics, 2007)
In this work we report the synthesis of the Pb(Fe_0.5Nb_0.5)O_3 (PFN) powders and sintered ceramics. The ceramics were prepared from oxides: Fe_2O_3, Nb_2O_5 and PbO by two-stage columbite method by calcination. PFN powders were dried and formed in samples in shape of discs (10×1) mm^3 and rectangular bars (26×10×1) mm^3. The samples were sintered by conventional ceramic sintering (CCS) method at temperature of 1323 K for 2 h in air. The density of the ceramic samples was determined to be ρ = 8200 kg/m^3. The obtained results of investigations of electric and mechanical properties such as: Young’s modulus E, electric permittivity ε and tangent of dielectric loss of angle tan δ of the Pb(Fe_0.5Nb_0.5)O_3 ceramics obtained are presented.